How to draw fantasy manga - Hawkins, Jack (Ultimate manga., 2016)
Offers step-by-step instructions for drawing a variety of fantasy manga characters, including a dragon, a mutant ogre, a monster, and a warrior monk. Includes color illustrations, a glossary, and further resources.